Analysis of innovations and practices in the cultivation of arracacha in Cajamarca, Colombia - Navarro-Niño, Diego Alberto; Jaramillo-Barrios, Camilo Ignacio (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The objective of this study was to analyze the adoption rate of innovations of the cultivation of arracacha in the municipality of Cajamarca, Tolima, Colombia. A simple random sampling design was used to select a sample of 104 producers from a known population with a 90% confidence level and a maximum permissible error of 10%. Twenty-eight crop-related innovations were evaluated, in addition to a producer characterization. The innovation adoption rate were calculated, in addition to a descriptive univariate and multivariate multiple correspondences statistical analysis. There was a trend towards the adoption of practices aimed at increasing productivity in arracacha cultivation, although the lack of technical assistance and rural extension services was evident, as well as the need to strengthen associativity processes and active farmer participation in learning processes.